2016
DOI: 10.1136/bcr-2016-217753
|View full text |Cite
|
Sign up to set email alerts
|

Successful improvement of Buschke-Löwenstein tumour in an HIV-infected patient with antiretroviral therapy alone

Abstract: Buschke-Löwenstein tumour (BLT), also defined as giant condyloma acuminatum, is a rare exophytic tumour affecting the anogenital and perianal regions associated with human papillomavirus (HPV) infections, with a potential of malignant transformation and which is at a greater risk in T-cell mediated immunodeficient patients. Different therapeutic options, alone or in combination, have been reported for the treatment of BLT including local therapy but wide surgical local excision is however recommended as the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Risk factors for VC are low socioeconomic status, drug abuse, sexually transmitted diseases, diabetes, and smoking [12]. A mechanism related to impaired immune response has been proposed, and anogenital VC in association with HIV infection has been described [14].…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for VC are low socioeconomic status, drug abuse, sexually transmitted diseases, diabetes, and smoking [12]. A mechanism related to impaired immune response has been proposed, and anogenital VC in association with HIV infection has been described [14].…”
Section: Discussionmentioning
confidence: 99%
“…These treatment modalities are less effective and associated with higher rates of recurrence compared to surgical resection. Grodner et al reported a case of Buschke–Löwenstein tumor that resolved with immune restoration with HAART and highlights the role of immunosuppression in pathogenesis [ 6 ]. In some cases, the tumor worsened with HAART initiation despite immune restoration [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most important risk factors include anal receptive sex, immunosuppression, HIV infection, chronic irritation and poor personal hygiene [1]. BLT is sometimes associated with severe morbidity due to its invasive growth which can result into local tissue destruction and occlusion of the rectum, especially in cases of malignant transformation into squamous cell carcinoma [6,7]. Histologically BLT has benign appearance with negligible cellular atypia, papillomatosis, koilocytosis and epithelial hyperplasia [1,2].…”
Section: Discussionmentioning
confidence: 99%